Cannabigerol Effect on Streptococcus mutans Biofilms—A Computational Approach to Confocal Image Analysis - Aqawi, Muna; Steinberg, Doron; Feuerstein, Osnat; Friedman, Michael; Gingichashvili, Sarah (Frontiers in Microbiology, 2022)
Biofilms are complex bacterial structures in which bacterial cells thrive as a community. Many bacterial species, including pathogens, form biofilms of high complexity and adaptability to a wide range of environmental conditions. One example of these is Streptococcus mutans, a gram-positive bacterium that has been associated with caries. Cannabigerol, a non-psychoactive cannabinoid, has been shown to affect Streptococcus mutans biofilms. In order to better characterize the effect of cannabigerol on biofilms of Streptococcus mutans, this paper provides a series of computational assays for biofilm analysis, applied on confocal images of Streptococcus mutans biofilms treated with cannabigerol. Confocal images are ubiquitous in biofilm analysis – they are often used to visualize the complex structure and molecular composition of biofilm macrocolonies. In this paper, we demonstrate how confocal imaging data can be used to reveal more comprehensive insights into biofilm structure and measure specific anti-biofilm effects. This is accomplished by a series of computational assays, each focusing on a different aspect of biofilm structure.